PERBEDAAN EFEKTIVITAS KOMBINASI ANALGESIK OPIOID PADA PASIEN PASCA OPERASI SESAR DI RSIA PUCUK PERMATA HATI DENPASAR - Anak Agung Ngurah Putra Riana Prasetya; Mahadri Dhrik; Putu Dian Marani Kurnianta (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Childbirth is the culmination of a series of pregnancies, one of the delivery methods is by caesarean section with common complaints after that being pain and difficulty in the mobility of the patient. This study aimed to determine the profile and effectiveness of combination therapy with opioid analgesics used to reduce pain after caesarean section based on the value of the Visual Analogue Scale (VAS). This research was conducted at RSIA Pucuk Permata Hati Denpasar. This study was conducted in a cross-sectional manner. This study used all medical record data for pregnant women who gave birth by caesarean section and had VAS values before and 6 hours after receiving opioid analgesic combination therapy in January-December 2021. Samples were taken using a probability sampling technique with a simple random sampling approach. Data were analyzed using the Kolmogorov-Smirnov test and the Kruskal-Wallis test to see differences in the effectiveness of combination analgesics therapy. Based on 183 samples (each group 61 samples), the highest age group was 21-30 years (52.46%), with the gestational age at 40 weeks (70.49%). The combination therapy with opioid-opioid (pethidine-morphine) has better effectivity based on the mean of lowering pain intensity with a VAS scale (2.05 ± 0.59). The normality test showed that the data were not normally distributed (p 0.05). The Kruskal-Wallis test showed that there was no significant difference (p-value 0.748 0.05) in the usage of three combination analgesics therapies to reduce pain in post-caesarean patients based on VAS values